Relationship between selenium intake, circulating selenium levels, and stroke: a systematic review and meta-analysis - Li, Yanyan; Ding, Rui; Pei, Xiaorui; Gao, Peng; Liu, Ziqi; Piao, Lifeng (Frontiers in Neurology, 2025)
BackgroundIschemic stroke represents the most prevalent form of cerebrovascular disease, which has a significant impact on people’s quality of life. Selenium is a crucial trace mineral with potential relevance for the prevention of cerebrovascular disease due to its antioxidant properties. Recent research has increasingly linked circulating selenium levels to the incidence of ischemic stroke, however, the findings remained inconsistent. The primary objective of our meta-analysis is to explore the potential relationship between circulating selenium levels and stroke as well as stroke mortality. In the meantime, the current study was done to evaluate the influence of dietary selenium intake on the risk of stroke.MethodsA comprehensive systematic search of electronic databases was conducted from inception through April 11, 2025, to identify relevant studies investigating the associations between circulating selenium levels, dietary selenium intake and ischemic stroke risk. Ultimately, 26 eligible studies were included in the meta-analysis.Results(1) The aggregated weighted mean difference (WMD) demonstrated that circulating selenium concentrations were markedly reduced in the ischemic stroke cohort relative to the control cohort (WMD = −0.13 [−0.20, −0.07]). (2) The multivariable-adjusted relative risk (RR) indicated that increased circulating selenium levels linked to a notable decrease in the risk of ischemic stroke (RR = 0.88 [0.83,0.92]), as well as a decreased risk of stroke mortality (RR = 0.86 [0.80, 0.93]). (3) Furthermore, our meta-analysis found that increased dietary selenium intake was adversely correlated with the risk of stroke, with RR of 0.87(0.76, 0.99). (4) A meta-analysis of dose–response curves revealed that circulating selenium levels were adversely linked with stroke.ConclusionThe level of circulation selenium is lower in ischemic stroke patients. There was an inverse association between the level of circulation selenium and the incidence of ischemic stroke as well as stroke mortality. Meanwhile, higher dietary selenium intake were shown to be negatively associated with ischemic stroke.